Land suitability evaluation for Curcuma zedoaria Rosc. in the community forest of the upstream Bengawan Solo watershed, Wonogiri, Indonesia - Widyatmani Sih Dewi; Supriyadi Supriyadi; Purwanto Purwanto; Aisyah Defara Rahmadani; Wahyu Galang Pranata; Ganjar Herdiansyah (Journal of Degraded and Mining Lands Management, 2023)
The soil in the upstream Bengawan Solo watershed is at high risk of degradation related to a high erosion rate. Finding the proper crop type with land suitability is critical to protect against further soil degradation. This study aimed to determine the land suitability of white turmeric (Curcuma zedoaria) and the limiting factors in the upstream Bengawan Solo watershed community forest. This research was descriptive-explorative based on a survey of four land map units (LMUs) of Sumberejo village (LMU1, LMU2, LMU3, and LMU4), Batuwarno, Wonogiri. The number of sample points at each LMU depended on the total area of the LMU and was repeated four times. LMU results from overlay soil type maps, administrative maps, rainfall maps, and slope maps. Land suitability assessment was analyzed using the matching method. The land suitability classes of the upstream Bengawan Solo for white turmeric were S3 eh, and N eh. The limiting factors on land suitability for white turmeric are erosion hazards and slopes. The efforts to improve the limiting factor can be made by contour cultivation and repairing the terrace.